PEMBERDAYAAN PEREMPUAN PADA SEKTOR EKONOMI KREATIF MELALUI KERAJINAN TANGAN RAJUT DAN SULAM EMBROIDERY - Bahtera, Novyandra Ilham; Purwasih, Rati; Darmawan, Budi (Universitas Mataram, 2024)
Human resource development must be fair and involve all levels of society including gender. Gender economic development involves the involvement of men and women as subjects of development, which must be equal. Gender inequality in development has created poverty in women's groups, making women powerless in the public sector. The poverty and powerlessness of women, which result from economic development that is not based on gender equality, can be reduced by increasing the role of women in economic development. Development strategies that can be a solution by increasing the role of women are women's empowerment, where women are given equal access and opportunities in the development process. One is women's empowerment based on the creative economy with knitting and embroidery crafts to create an increase in hard and soft skills in producing products of economic value. Partners in community service activities are women who are members of the Family Welfare Empowerment (Pemberdayaan Kesejahteraan Keluarga / PKK) of Desa Kace Timur, and the theme carried out in the service activities is women’s empowerment based on the creative economy through knitting and embroidery crafts. The results of the training transmission and embroidery activities showed an increase in the ability of training participants to produce knitted or embroidered products; thus, it had great potential to create a creative economy in women's groups who were members of the Family Welfare Empowerment group in Desa Kace Timur.